FRI0700 Physical activity decreased significantly but moderately during weeks where patients reported flares: a 3-month study of 170 rheumatoid arthritis (RA) or axial spondyloarthritis (AXSPA) patients wearing an activity tracker. (15th June 2017) - Jacquemin, C; Servy, H; Molto, A; Sellam, J; Foltz, V; Gandjbakhch, F; Hudry, C; Mitrovic, S; Fautrel, B; Gossec, L
Abstract : Background: RA and axSpA natural history comprises periods of low disease activity and flares. There is much interest in the concept of flares. Studies have indicated flares may alter patient quality of life, however, there are few data linking flares to quantifiable outcomes. Objectives: The objective was to assess longitudinally the association between patient-reported flares and physical activity assessed objectively using an activity tracker. Methods: This prospective multi-center observational study (ActConnect) included patients with definite RA (ACR/EULAR criteria) or axSpA (ASAS criteria) owning a smartphone. Physical activity was assessed continuously over 3 months by the number of steps using an activity tracker, and flares were self-assessed weekly using a specific flare question ("has your disease flared up during the last 7 days?")[1] with a categorical response according to: no flare, 1 to 3 days flare, or >3 days flare. The relationship between flares and physical activity for each week (time point) was assessed by linear mixed models adjusted on rheumatic disease, sex, age, obesity, biologics and employment status. Results: 170/178 patients (91 RA and 79 axSpA patients; 1553 time points) were analyzed: mean age 45.5±12.4 years, mean disease duration 10.3±8.7 years; 60 (35.3%) were males and 90 (52.9%) received biologics. Disease was well-controlled (mean DAS28: 2.3±1.2; mean BASDAI: 3.3±2.1). Physical activity was moderate (mean steps/day, 7067±2770). Flares were frequent (25.5% of the questionnaires); most (76.8%) were of short duration. Flares, in particular >3 days flares, were independently associated with less weekly physical activity (p=0.02–0.03), leading to a relative decrease of physical activity of 12–21% and an absolute decrease ranging from 836 to 1462 steps/day (Table 1 ). Conclusions: Flares were frequent in these low-disease patients, though most flares were of short duration. Flares were related to a moderate decrease in physical activity, confirming objectively the functional impact of patient-reported flares. References: VP Bykerk et al, RMD Open, 2016; 2:e000225.doi:10.1136/rmdopen-2015–000225. Disclosure of Interest: None declared